A Semantic Study of Connotative Meaning in Television Advertisement Messages - Cinta Yulistra Tindaon; Bernieke Anggita Ristia Damanik (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to explore the connotative meanings embedded in television advertisement messages through a semantic approach. As a form of mass communication, advertisements do not only convey messages directly (denotatively), but also imply additional meanings that can influence the audience’s emotions, perceptions, and behavior. In this research, the author examines several television advertisements from various product categories—such as food, beverages, beauty products, and digital services—by focusing on the use of symbolism, word choice, and cultural context that shape connotative meanings. The research method employed is descriptive qualitative with content analysis techniques. The findings indicate that connotative meanings in advertisements are often used to build a positive image, evoke emotional responses, and enhance product appeal through associations with social, cultural, and psychological values. These results highlight the importance of understanding connotative meanings in order to foster media literacy and critical awareness of messages received through television broadcasts